UNIT 1E.7 Quantifying Epithelial Early Common Progenitors from Long‐Term Primary or Cell Line Sphere Culture. (4th November 2015) - Clément, Flora; Zhu, Helen He; Gao, Wei‐Qiang; Delay, Emmanuel; Maguer‐Satta, Véronique
Abstract : Here, a protocol to quantify epithelial early common progenitor/stem cells grown as spheres in non‐adherent culture conditions is described. This protocol is based on the combination of two functional tests: the sphere assay to maintain and enrich early progenitor/stem cells, and the epithelial colony‐forming cells (E‐CFC) assay to identify and quantify further differentiated epithelial progenitors. Primary spheres mainly contain progenitors and rare stem/early common progenitor cells while secondary and tertiary spheres contain progenitor cells derived from the early common progenitor/stem cell population maintained through passages and partially differentiated. Spheres are enzymatically and mechanically dissociated; the derived cells are subsequently plated on irradiated NIH‐3T3 fibroblasts for further processing, as in the E‐CFC assay. The principle of this assay is to quantify the number of epithelial colonies generated by cells present in the different sequential spheres. This assay has therefore been named the early common progenitor‐derived colonies assay (ECP‐DC). © 2015 by John Wiley & Sons, Inc.